ANALISIS SISTEM DAN PROSEDUR AKUNTANSI PENGELUARAN KAS UANG PERSEDIAAN PADA DINAS KESEHATAN KABUPATEN SIDENRENG RAPPANG - Maghfirah, Annesa Tasya; Sahade, Sahade; Anwar, Azwar (LPPM Universitas Bina Bangsa, 2025)
This research aims to analyze the conformity of the accounting system and procedures for cash disbursement of supplies with the Minister of Home Affairs Regulation (Permendagri) Number 77 of 2020 at the Sidenreng Rappang District Health Service.The focus of this research is to analyze the systems and procedures for disbursing cash supplies at the Sidenreng Rappang District Health Service to see whether they comply with the applicable regulations set out in Minister of Home Affairs Regulation (Permendagri) Number 77 of 2020. The data collection techniques used are observation, interviews and documentation. The data analysis technique used in this research is descriptive qualitative. The results of this research show that the implementation of the accounting system and procedures for cash disbursement of supplies at the Sidenreng Rappang District Health Service is in accordance with Minister of Home Affairs Regulation (Permendagri) Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management. The implementation of cash disbursements has been supported by related documents, namely Fund Provision Letter (SPD), Payment Request Letter (SPP), Payment Order (SPM), Fund Disbursement Order (SP2D), and Accountability Letter (SPJ).